MENJADI GARAM DAN TERANG PERSPEKTIF MATIUS 5: 13-16 DAN INSPIRASI BAGI KERASULAN AWAM KATOLIK - Senda, Siprianus Soleman; Fereinto, Redemptus Mario (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The expression salt and light of the world in the text of Matthew 5:13-16 is interpreted allegorically as the value of the gospel that is lived throughout life. This value is lived by carrying out the three tasks of Christ as priest, prophet and king in the general priesthood based on the sacrament of baptism. This means that the mission to become salt and light of the world is also carried out by the laity. This ideal insight still has a gap in practice. This happens because of the lack of literacy of the laity about the duties of the general priesthood as priest, prophet and king received based on the sacrament of baptism. This article discusses this problem by examining the text of Matthew 5:13-16 about salt and light of the world. The research method used is the literature review method with descriptive analysis of the allegorical meaning of salt and light of the world, and its inspiration for the mission of the laity in the world order. The result is a growing understanding among the laity to realize their mission in the perspective of becoming salt and light of the world. This understanding will lead to a missionary praxis that is increasingly evident.